2021
DOI: 10.3390/cancers13153831
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination of Bevacizumab with Chemotherapy Improves Therapeutic Effects for Advanced Biliary Tract Cancer: A Retrospective, Observational Study

Abstract: Background: Biliary tract cancer (BTC) is a heterogenous collection of biliary tract cancer at different primary sites, and the prognosis of advanced BTC is dismal. Systemic chemotherapy with gemcitabine and cisplatin (GC) has been the reference regimen since 2010. How to improve therapeutic effects of GC regimen is an urgent mission at present. Methods: Bevacizumab with a reduced dosage and modified schedule (10 mg/Kg/triweekly, 1 day before GS at the first 2 cycles) was combined with standard GC for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…While all cholangiocarcinoma subtypes share several somatic mutations, including TP53 and KRAS, recent next-generation sequencing has identified unique genetic aberrations dependent on the CCA subtype [ 62 ]. While most sequencing studies group HC and distal CCA together for analysis, one study suggested that HC has a distinct molecular subtype [ 63 ]. High-frequency HC subtype-specific mutations include TP53, KRAS, mTOR, ABL1, NOTCH1, PBRM1, PIK3CA, ARID1A, NF1, and EGFR [ 64 ].…”
Section: Systemic Therapymentioning
confidence: 99%
“…While all cholangiocarcinoma subtypes share several somatic mutations, including TP53 and KRAS, recent next-generation sequencing has identified unique genetic aberrations dependent on the CCA subtype [ 62 ]. While most sequencing studies group HC and distal CCA together for analysis, one study suggested that HC has a distinct molecular subtype [ 63 ]. High-frequency HC subtype-specific mutations include TP53, KRAS, mTOR, ABL1, NOTCH1, PBRM1, PIK3CA, ARID1A, NF1, and EGFR [ 64 ].…”
Section: Systemic Therapymentioning
confidence: 99%